Income, housing wealth, and private school access in Britain. Issue 3 (4th May 2021) - Henseke, Golo; Anders, Jake; Green, Francis; Henderson, Morag
ABSTRACT: Access to Britain's highly-resourced private schools matters because of concerns surrounding social mobility. Using the UK Family Resources Survey, we document a high and mostly stable income concentration of private school access since 1997. Nevertheless, some low-income participation persists. Bursaries are income-progressive but cannot account for this participation. Housing wealth is, however, found to be greater for private school participants. We estimate that a 10 per cent rise of family income and home value raises private school participation by 0.9 points, respectively. Neither effect changes over time. The income effect, however, falls sharply outside the top income decile.